2014
DOI: 10.1016/j.ejrad.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

3D dynamic pituitary MR imaging with CAIPIRINHA: Initial experience and comparison with 2D dynamic MR imaging

Abstract: 3D dynamic pituitary MR provided better identification and higher normalized values of pituitary posterior lobe and stalk than 2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Dynamic MRI is usually performed with a fast SE coronal section, but if the microadenoma is located at the anterior or posterior end of the anterior lobe, the partial volume effect may make the diagnosis difficult. In such cases, three-dimensional (3D) dynamic MRI [39][40][41][42] or dynamic MRI with simultaneous acquisition of coronal and sagittal images [43] may be useful.…”
Section: Routine Mrimentioning
confidence: 99%
“…Dynamic MRI is usually performed with a fast SE coronal section, but if the microadenoma is located at the anterior or posterior end of the anterior lobe, the partial volume effect may make the diagnosis difficult. In such cases, three-dimensional (3D) dynamic MRI [39][40][41][42] or dynamic MRI with simultaneous acquisition of coronal and sagittal images [43] may be useful.…”
Section: Routine Mrimentioning
confidence: 99%
“…Secondly, the number of focal lesions in our present patient cohort was not sufficient to perform a quality assessment for conspicuity evaluation of focal pathologies. Previous studies on CAIPIRINHA demonstrated robust pancreatic imaging and better delineation of organ outlines with CAIPIRINHA, as compared to GRAPPA-accelerated 2D FLASH imaging [ 12 ], better identification of stalk and posterior lobe of the pituitary gland with dynamic CAIPIRINHA-accelerated scans [ 15 ], and better vessel clarity, lesion conspicuity, and edge sharpness in liver scans of adult patients [ 6 ]. From our clinical experience we know that HASTE imaging with its fast “one-slice-per-shot” acquisition in combination with breathing-related motion in the upper abdomen can lead to incomplete volume coverage, so that, for example, small liver lesion may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced techniques that enable volumetric dynamic imaging with thin slices are becoming more available (43,35). These approaches may prove to be alternate approaches that can minimize partial volume averaging, and decrease ambiguity in determining contrast enhancement.…”
Section: Discussionmentioning
confidence: 99%